Enhancing the Impact of Online Learning: A Comparative Analysis of MOOC Platforms and a Proposed Open-Source Arabic Platform - Basil, Ala’a; Aldabbagh, Mohammad A. Taha (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Since a few years ago, online learning platforms like Coursera and edX have grown a lot and now have close to 200 million users, especially after the COVID-19 pandemic. Even though these platforms reach a lot of people, they don’t have as much of an effect because learners don’t use them much. In traditional face-to-face classrooms, teachers try to get students interested by asking them to take part in class discussions and talk about themselves and their ideas. But it’s not clear how well these strategies work on online learning platforms. This paper examines and compares e-learning platforms, especially those associated with MOOCs. It also includes a proposal for an Arabic and open-source educational platform affiliated with the University of Mosul.